PENINGKATAN HASIL BELAJAR TEMA KEGEMARANKU MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING - Elly Sukmanasa; Danti Damayanti (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
The research with classroom action research approach is carried out in collaboration and cycles. It is conducted in class 1A Ciheuleut 2 Elementary School, Bogor Timur with the aims of describing learning outcomes level of success in Tema 2 Kegemaranku, Sub-tema 4 Gemar Membaca Pembelajaran ke 3 through scientific approach by applying discovery learning model. The subjects of this study are a teacher with 31 students in the odd semester 2018/2019 school year. The first cycle result showed that the average value of learning outcomes of the students who achieved completeness is 16 students (48%), while 15 students (32%) have not. Meanwhile, In the second cycle there are 27 students (87%) who achieved completeness, and 4 students (13%) have not yet achieved it yet. In the first cycle learning process, the students changing behavior values were 48% which was considered good enough, and in the second cycle the average score is 80% with good category. From the results of this study it can be concluded that the application of discovery learning in Tema 2 Kegemaranku, Subtema 4 Gemar Membaca, Pembelajaran 3 in class 1A Ciheuleut 2 Elementary School, Bogor Timur improves the changes of students behavior.